Retained avidity despite reduced cross-binding and cross-neutralizing antibody levels to Omicron after SARS-COV-2 wild-type infection or mRNA double vaccination - Harthaller, Teresa; Falkensammer, Barbara; Bante, David; Huber, Maria; Schmitt, Melanie; Benainouna, Habib; Rössler, Annika; Fleischer, Verena; von Laer, Dorothee; Kimpel, Janine; Würzner, Reinhard; Borena, Wegene (Frontiers in Immunology, 2023)
Introduction The rapid evolution of SARS-CoV-2 has posed a challenge to long-lasting immunity against the novel virus. Apart from neutralizing function, binding antibodies induced by vaccination or infection play an important role in containing the infection. Methods To determine the proportion of wild-type (WT)–generated antibodies recognizant of more recent variants, plasma samples from either SARS-CoV-2 WT-infected (n = 336) or double-mRNA (Comirnaty)–vaccinated individuals (n = 354, age and sex matched to the convalescent group) were analyzed for binding antibody capacity against the S1 protein of the BA.1 omicron variant. Results Overall, 38.59% (95% CI, 37.01– 40.20) of WT-generated antibodies recognized Omicron BA.1 S1 protein [28.83% (95% CI, 26.73–30.91) after infection and 43.46% (95% CI, 41.61–45.31) after vaccination; p < 0.001]. Although the proportion of WT-generated binding and neutralizing antibodies also binding to BA.1 is substantially reduced, the avidity of the remaining antibodies against the Omicron variant was non-inferior to that of the ancestral virus: Omicron: 39.7% (95% CI: 38.1–41.3) as compared to the avidity to WT: 27.0% (95% CI, 25.5–28.4), respectively (p < 0.001). Furthermore, we noticed a modestly yet statistically significant higher avidity toward the Omicron epitopes among the vaccinated group (42.2%; 95% CI, 40.51–43.94) as compared to the convalescent counterparts (36.4%; 95% CI, 33.42–38.76) (p = 0.003), even after adjusting for antibody concentration. Discussion Our results suggest that an aspect of functional immunity against the novel strain was considerably retained after WT contact, speculatively counteracting the impact of immune evasion toward neutralization of the strain. Higher antibody levels and cross-binding capacity among vaccinated individuals suggest an advantage of repeated exposure in generating robust immunity.